Leaf gall diseases from Nanded district of Maharashtra - Gawate, A B; Papdiwal, P B (Journal of Phytology, 2011)
The study of plant galls has gained a significant importance in the field of plant pathology. The galls are produced by bacteria, fungi and insects. The galls produced on trees under the influence of insect parasites are characteristic. During the survey of plant diseases, 11 species of trees viz Azadirachta indica, Cardia sinensis, Cassia fistula, Ficus racemosa, Hardwickia binata, Leucaena leucacephala, Mangifera indica, Pongamia pinnata, Syzygium cumini, Semicarpus anacardium and Zizyphus mauritiana were found to suffer from galls in Nanded district. These were found to be caused by insects. A brief report of this investigation is presented in this paper. <!–EndFragment–>